Tra regole ed eccezioni La messa in opera delle politiche pubbliche in Italia - MORISI, MASSIMO (Lectio Magistralis, 2016)
In Italy, public policies have difficult processing, and even more difficult implementation. It is normal for a number of unexpected side effects to occur as a result of a public policy. Likewise, it is normal that a public policy determines an impact which is appreciated ex post, but cannot be identified with the original, designed one. So much so that many policies resemble a bet, rather than a project. In other words, they are always exposed to a universe of factors and circumstances which may destroy or change their theoretical assumptions, independently from any effective and measurable government capacity. This is the sign of a democratic regime's structural fragility and of the government capacity expressed by it: its difficulty in feeding its policies with sufficient legitimizing doses and tools in order for the policies to achieve the desired effectiveness. It is a classic theme for political science; in this volume, it is revisited in the light of the different types of empirically conceivable legitimization and of the contemporary state's ability to produce social regulation.